After The Wall : Art and Culture in post-Communist Europe - Adams, Bradley; Andjelkovic, Branislava; Andreeva, Ekaterina; András, Edit; Andrási, Gabor; Angel, Judit; Backstein, Joseph; Balaci, Ruxandra; Balassanian, Edward; Becker, Kathrin; Bencsik, Barnabás; Beros, Nada; et al. (Stockholm : Moderna museet, 1999)
Academic Training Group ; AES ; Agostini, Edi Hila ; Alksnins, Arvids ; Antoshina, Tatyana ; Arsen Savadov & Oleksandr Kharchenko ; Benczúr, Emese ; Boyadjiev, Luchezar ; Braila, Pavel ; Breda Beban & Hrvoje Horvatic ; Bromová, Veronika ; Bubelyté, Violeta ; C.U.K.T. ; Cekic, Jovan ; Cernicky, Jiri ; Cerny, David ; Csorgo, Attila ; Dakic, Danica ; Dimitrova, Iskra ; El-Hassan, Róza ; Erhardt Miklos & Dominic Hislop ; Fishkin, Vadim ; Förster, Gunda ; Gabrans, Gints ; Giedrius Kumetaitis & Mindaugas Ratavicius ; Gorlova, Lyudmila ; Gradinaru, Cosmin ; Group, Fast Reaction ; Guryanov, Georgy ; Hadzifejzovic, Jusuf ; Haxhilliari, Besnik & Flutura ; IRWIN ; Ivekovic, Sanja ; Janin, Zuzanna ; Jaros, Piotr ; Josing, Inessa ; Kaljo, Kai ; Kapanadze, Keti ; Kimelis, Peteris ; Kintera, Kristof ; Kiraly, Josif ; Kizny, Tomasz ; Klinov, Artur ; Kozhemyakin, Sergey ; Kozyra, Katarzyna ; Kristev, Rassim ; Kulik, Oleg ; Kulik, Zofia ; Lakner, Antal ; Leiderman, Yuri ; Lejman, Dominik ; Levchenya, Vitold ; Lewandowsky, Via ; Libera, Zbigniew ; Licis, Dzintars ; Licul, Maja ; Lieberman, Tanya ; Lilia Dragneva & Lucia Macari ; LN Women's League Project ; Lomaschwili, Nikolos ; Man, Calin ; Marina Grzinic & Aina Smid ; Markovic, Milovan ; Martinis, Dalibor ; Mikhailov, Boris ; Miroslav Kulchitsky & Vadim Checkorsky ; Moskaleva, Galina ; Moukhin, Igor ; Mumin, Milan ; Nagy, Kriszta ; Narkevicius, Deimantas ; Naskovski, Zoran ; Németh, Ilona ; Nicolai, Olaf ; Novickas, Audrius ; Ondák, Roman ; Peljhan, Marko ; Perjovschi, Dan ; Plamen Dejanov & Swetlana Heger ; Pormale, Monika Ines ; Puder, Ulf ; Purg, Franc ; Rakauskaité, Eglé ; Ramischwili, Koka ; Ratniks, Martins ; Rauch, Neo ; Ronai, Peter ; Rumas, Robert ; Sala, Anri ; Salakhova, Aidan ; Sargsvan, Azat ; etc.
Volume 2: After The Wall : Art and Culture in post-Communist Europe, 259 p. : ill. (teksten)
After The Wall : Art and Culture in post-Communist Europe, Moderna Museet, Stockholm, 16 October 1999 - 16 January 2000 ; Ludwig Museum of Contemporary Art, Budapest, 15. June - 27. August 2000
Engels
kunstcatalogus